Innovative Approaches in the Development of Book Trade and Their Theoretical Problems - Usmanova Nigina Marupovna (Genius Journals, 2022)
The article is based on the need for innovative approaches and factors for the development of the book trade. At the moment, special importance is attached to innovative methods that are included in the existing book trade for the development of the book trade. A comparative analysis of the situation of bookselling in some regions of our country has also been carried out and, based on the results of the study, some recommendations for the development of this industry have been given
Keywords: Book; bookselling; innovations; innovative factors